2018
DOI: 10.1002/env.2499
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regression with an informatively missing covariate: Application to mapping fine particulate matter

Abstract: The United States Environmental Protection Agency has established a large network of stations to monitor fine particulate matter of <2.5 µm (PM2.5) that is known to be harmful to human health. Unfortunately, the network has limited spatial coverage, and stations often only measure PM2.5 every few days. Satellite‐measured aerosol optical depth (AOD) is a low‐cost surrogate with greater spatiotemporal coverage, and spatial regression models have established that including AOD as a covariate improves the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The average number of MISR retrievals is around 30 per year across grid cells, and regulatory monitors typically provide measurements every 6 days. To gap-fill predictions, recent studies for total PM 2.5 mass considered imputing total AOD that was informatively missing [ 38 , 39 ] and ensemble modeling that included members without AOD as a predictor [ 40 ]. Both approaches warrant further investigation for predicting PM 2.5 components and for BART.…”
Section: Discussionmentioning
confidence: 99%
“…The average number of MISR retrievals is around 30 per year across grid cells, and regulatory monitors typically provide measurements every 6 days. To gap-fill predictions, recent studies for total PM 2.5 mass considered imputing total AOD that was informatively missing [ 38 , 39 ] and ensemble modeling that included members without AOD as a predictor [ 40 ]. Both approaches warrant further investigation for predicting PM 2.5 components and for BART.…”
Section: Discussionmentioning
confidence: 99%
“…AOD is a proxy measurement of particle air pollution data since it measures light extinction due to particles in the atmospheric column. We consider the regression model with PM 2.5 as the response variable and AOD as the covariate since AOD was shown in previous studies to have positive impacts on PM 2.5 (Chu et al, 2016;Grantham et al, 2018;Ma et al, 2016;Yu et al, 2017). The study domain covers the Northeastern United States (Connecticut, Delaware, Maine, Maryland, Massachusetts, New Hampshire, New Jersey, New York, Pennsylvania, Rhode Island, Vermont, and District of Columbia), which is defined by the National Climatic Data Center (Karl & Koss, 1984).…”
Section: Data Applicationmentioning
confidence: 99%
“…The satellite-derived aerosol optical depth (AOD) is a proxy measurement of particle air pollution data since it measures light extinction due to particles (e.g., dust, smoke, pollution) in the atmospheric column. Previous studies showed that PM 2.5 concentrations have positive associations with AOD (Chu et al, 2016;Grantham et al, 2018;Ma et al, 2016;Yu et al, 2017). For spatial data, it is often assumed that regression coefficients are homogeneous across the entire spatial domain of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on predicting PM 2.5 concentration from AOD were reviewed by Chu et al (2016). In addition, those regression-based models showed that PM 2.5 concentrations have positive relationships with AOD (Chang, Hu, & Liu, 2013;Grantham, Reich, Liu, & Chang, 2018;Kloog, Koutrakis, Coull, Lee, & Schwartz, 2011;Kloog, Nordio, Coull, & Schwartz, 2012;Lee, Liu, Coull, Schwartz, & Koutrakis, 2011;Liu, Sarnat, Kilaru, Jacob, & Koutrakis, 2005;Ma et al, 2016;Paciorek, Liu, Moreno-Macias, & Kondragunta, 2008;Yu, Liu, Ma, & Bi, 2017) because AOD measures light extinction due to particles (e.g., dust, smoke, and pollution) in the atmospheric column. We also obtain satellite-measured AOD data for the Northeastern United States from the Moderate Resolution Imaging Spectroradiometer in order to investigate its relationship to the PM 2.5 concentrations in the fused CMAQ data via our mixed-effects model with spatial block-wise random effects.…”
Section: Data Descriptionmentioning
confidence: 99%